Heavy Metals Concentration in Padina sp. (seaweed) and Halodule pinifolia (seagrass) of Sampadi Island, Sarawak - Nuranisah, binti Ajmain (Universiti Malaysia Sarawak(UNIMAS), 2013)
The aims of this study were to determine the concentrations of Manganese (Mn), Iron (Fe), Aluminium (Al), Lead (Pb), Zinc (Zn), Nickel (Ni), Cobalt (Co), Cadmium (Cd), Chromium (Cr), Copper (Cu) and Mercury (Hg) and to find out the differences of these metals Bioaccumulation Factor (BAF) in Padina sp. (seaweed) and Halodule sp.(seagrass) that grow in Sampadi Water. Two stations were chosen for seaweed sampling and one station was chosen for seagrass and sediment. The concentration levels of the selected metals were determined by using Atomic Absorption Spectroscopy (AAS) and Hg was analysed using Flow Injection Mercury System (FIMS 400) analyzer. Two seaweed species were identified as Padina sp. (Padina Minor Yamada and Padina Tetrastomatica Hauck) and seagrass species found was Halodule. Metal concentration found in Station 1 for July is Fe (4911 mg/kg)>Al (3664.04 mg/kg)>Mn (345.38 mg/kg)>Zn (126.89 mg/kg)>Cr (84.46 mg/kg)>Ni (15.81 mg/kg) >Hg (0.20 mg/kg); Station 1 November Al (11 030.44 mg/kg)>Fe (5362.22 mg/kg)>Mn (178.97 mg/kg)>Zn (124.93 mg/kg)>Cr (88.93 mg/kg)>Ni (16.80 mg/kg)>Hg (0.12 mg/kg). In Station 2 July, Al (10 589.98 mg/kg)>Fe (5898.89 mg/kg)>Mn (487.36 mg/kg)>Cr (164.76 mg/kg)>Zn (47.88 mg/kg)>Ni (41.29 mg/kg) and in November is Al (14 207.78 mg/kg)>Fe (6010 mg/kg)>Mn (204.73 mg/kg)>Cr (167.66 mg/kg)>Zn (144.19 mg/kg)>Ni (43.89 mg/kg). Metal Concentration found in seagrass is Al (1732.51 mg/kg)>Fe (1533 mg/kg)>Mn (408.52 mg/kg)>Cr (66.75 mg/kg)>Zn (63.08 mg/kg)>Ni (11.09 mg/kg) and in sediment is Fe (9627 mg/kg)>Al (1368 mg/kg)>Mn (241.02 mgkg)>Cr (44 mg/kg)>Zn (37.65 mg/kg)>Ni(7.99 mg/kg). The BAF Value for seaweed in Station 1 for July range from 0.51-3.57, in November range from 0.51-52.64. In Station 2 the range from 0.61-7.74 in July and in November the value range from 5.34-140.25. BAF values in seagrass range from 1.27 -1.68.